Communicative Language Teaching in CEFR-Based English Learning - Trimadona, Eliza; Amalia, Shynta; Sumardi, Mayang Sastra; Pratama, Aryawira; Saputri, Vioni (Journal of English Education and Teaching, 2024)
The objective of this study is to evaluate and enhance the effectiveness of Communicative Language Teaching in the context of CEFR-based English language learning. The population consisted of students from State Junior High School (SMPN) 8 in Jambi. The samples were collected using convenience sampling. A total of 32 students participated in this study. This investigation utilized a quantitative research approach with a pre-experimental design. The CEFR Test was utilized as an assessment tool for data collection. Three primary methodologies were employed in this investigation. The study consisted of pre-test, treatment procedures, and post-test assessments. The pretest was administered to assess the students' proficiency in spoken English according to the CEFR standard. Subsequently, the researchers administered eight rounds of treatments utilizing Communicative Language Teaching. The concluding phase involved administering a post-test to determine if there was any improvement in students’ performance. The researchers analyzed the results of the pre-test and post-test following the implementation of the Communicative Language Teaching treatment in CEFR-based English learning. The two-tailed significance value obtained from the calculation of the paired samples t-test was 0.017, which is less than the significance level of 0.05. The value of this computation can be interpreted as the progressive improvement in student performance resulting from the implementation of Communicative Language Teaching in CEFR-based English education.